2007
DOI: 10.1186/1748-717x-2-39
|View full text |Cite
|
Sign up to set email alerts
|

Radical stereotactic radiosurgery with real-time tumor motion tracking in the treatment of small peripheral lung tumors

Abstract: Background: Recent developments in radiotherapeutic technology have resulted in a new approach to treating patients with localized lung cancer. We report preliminary clinical outcomes using stereotactic radiosurgery with real-time tumor motion tracking to treat small peripheral lung tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 29 publications
3
78
1
Order By: Relevance
“…In these cases, bronchoscopic or intravascular marker placement provides a solution. Our complication rate after marker placement was acceptably low (5%) even when compared to complications in younger populations (16-28%) [40,41]. Treatment was also tolerated well by octogenarians despite treatment times of approximately 90 min.…”
Section: Discussionmentioning
confidence: 59%
“…In these cases, bronchoscopic or intravascular marker placement provides a solution. Our complication rate after marker placement was acceptably low (5%) even when compared to complications in younger populations (16-28%) [40,41]. Treatment was also tolerated well by octogenarians despite treatment times of approximately 90 min.…”
Section: Discussionmentioning
confidence: 59%
“…Although the incidence of toxicity is not mentioned by Langendijk et al (15), the low incidence of toxicity after SRT may be the reason why symptom scores did not increase in our study. The risk of late toxicity is small (2-8%) after treating patients with SRT, as treatment volumes are generally small (4,12,16). On the other hand, the risk of toxicity after stereotactic irradiation of central tumors is not negligible (17) and may influence the patient's QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple Phase I and II SBRT studies of the treatment of Stage I-II NSCLC have reported chest wall (CW) pain and/ or rib fracture as a part of the toxicity profile (6)(7)(8)(9). CW pain can be transient or can last several weeks or longer.…”
Section: Introductionmentioning
confidence: 99%